2007
DOI: 10.1593/neo.07334
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of β-Catenin Localization with Cyclooxygenase-2 Expression and CpG Island Methylator Phenotype (CIMP) in Colorectal Cancer

Abstract: The WNT/beta-catenin (CTNNB1) pathway is commonly activated in the carcinogenic process. Cross-talks between the WNT and cyclooxygenase-2 (COX-2 or PTGS2)/prostaglandin pathways have been suggested. The relationship between beta-catenin activation and microsatellite instability (MSI) in colorectal cancer has been controversial. The CpG island methylator phenotype (CIMP or CIMP-high) with widespread promoter methylation is a distinct epigenetic phenotype in colorectal cancer, which is associated with MSI-high. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 44 publications
8
68
0
Order By: Relevance
“…As a positive stimulus of bone formation, COX2 is a known target of mechanical stimulation in bone cells (10,12) and is itself regulated by ␤-catenin (21). Indeed, ␤-catenin activates COX2 transcription in gastrointestinal cells (19,54,55). Thus, although we expected that in MSC that COX2 would be regulated by mechanical strain and have demonstrated that here (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…As a positive stimulus of bone formation, COX2 is a known target of mechanical stimulation in bone cells (10,12) and is itself regulated by ␤-catenin (21). Indeed, ␤-catenin activates COX2 transcription in gastrointestinal cells (19,54,55). Thus, although we expected that in MSC that COX2 would be regulated by mechanical strain and have demonstrated that here (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…For example, high nuclear β catenin percentage staining was found in 56% (126 of 226) of MSS cases compared with 3% (1 of 30) of MSI cases; P < .001. Differential WNT pathway activation, as evidenced by nuclear translocation of β catenin, has been previously shown in MSS versus MSI CRC in a number of cross-stage studies 37,38 ; however, this is the first time it has been demonstrated in a study focusing solely on stage II CRC. Our finding of more frequent tumor budding and increased nuclear β catenin in MSS compared with MSI CRC is consistent with previous reports and suggests that increased WNT pathway activation in MSS colorectal cancer may at least partly explain the difference in prognosis observed between these two molecular subtypes of colorectal cancer.…”
Section: Discussionmentioning
confidence: 61%
“…To compare the frequencies of methylation index 4-10 (or [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] in CACNA1G, for example, we limited the denominator to tumors with CACNA1G methylation index 44 (methylation positive) ( Table 1). This was because, compared to CIMP-high tumors, CIMP-low tumors had a higher proportion of tumors negative for CACNA1G methylation (methylation index o4), which, if included in the denominator, would have by itself decreased Table 1).…”
Section: Low-level Methylation At An Individual Promoter Was Common Imentioning
confidence: 99%
“…1,3 CIMPhigh colorectal tumors have a distinct clinical, pathologic and molecular profile, such as associations with proximal tumor location, female sex, poor tumor differentiation, inactive WNT/b-catenin (CTNNB1) and high BRAF and low TP53 mutation rates, [4][5][6] independent of microsatellite instability status. [7][8][9][10] Although controversial, CIMP may have prognostic implications in colorectal cancer. [11][12][13][14] In contrast to CIMP-high in colorectal cancer, the concept of CIMP-low (with less widespread CIMPspecific promoter methylation) is still emerging.…”
mentioning
confidence: 99%